Genome-wide association study reveals candidate genes for litter size and function validation of MMP16 gene in lop sheep - Wang, Jieru; Bi, Lanshu; chen, Hong; Li, Xiaopeng; Khamili, Abliz; Kurban, Waili; Yang, Chenchen; Niu, Peng; Huang, Fei; Fang, Di; Han, Chunmei; Gao, Qinghua (Frontiers in Veterinary Science, 2025)
As a premium indigenous sheep breed endemic to Tarim Basin, Xinjiang, China, Lop sheep demonstrate remarkable adaptability to extreme arid, high-temperature and sandstorm-prone environments, with some ewes exhibiting exceptional prolificacy. To elucidate the genetic regulation of this reproductive trait, we integrated whole-genome resequencing and transcriptome sequencing, conducting genome-wide association study on 110 Lop ewes with particular emphasis on the regulatory role in litter size determination of MMP16 gene. Through multi-dimensional investigations including qRT-PCR, immunohistochemistry, ovarian granulosa cells culture, and transcriptome sequencing, we revealed that MMP16 gene significantly influences folliculogenesis and ovulation by modulating extracellular matrix (ECM) remodeling and PI3K-AKT signaling pathway activation. Our research systematically elucidates genetic variations associated with prolificacy in Lop sheep and deciphers the biological function of MMP16 gene, providing novel insights into the genetic architecture of ovine reproductive traits. The findings establish a theoretical foundation for molecular marker-assisted breeding and the exploitation of superior germplasm resources.